A super low band-gap IR dye realized 360° omnibearing and all optical wavelength photo-detection. (January 2021) - Qin, Ruiping; Hu, Lianghao; Guo, Deen; Li, Miao; Yang, Jien; Liu, Hairui; Jiang, Yurong; Song, Jian
Abstract: Common photo-detectors can easily detect the front light source, but it has no response for the rear incident light. If the light source comes from back, to obtain the photo-electric signal, the detector has to turn certain angles to track the light source and this will inevitably cost more time or need complicated mechanical system. Here, a solution-processed photo-detector is reported what is based on a new low band-gap all fused infrared (IR) dyes: N-hybridized hexarylenetetracarboxylic bisimides (NHAB). The detector has 360° omnibearing and a wide photo-electric response spectral range from 300 to 1200 nm. Operating at room temperature and zero bias, the device detectivity at 405 nm is 1.65 × 10 12 Jones and a maximum responsivity 189 mA/W at twelve o'clock direction, a moderate responsivity 34 mA/W at six o'clock direction. Graphical abstract: a new infrared dye for all optical wavelength photo-detect. Image 1 Highlights: Report a new super low band-gap IR dye. Fabricate 360° omnibearing photo-detector. Response spectral range from 300 to 1200 nm.